Regulasi Diri dan Pembelian Impulsif Remaja Akhir Penggemar K-Pop dalam Membeli Merchandise K-Pop - Padji, Erly Marcella; Rahayu, Maria Nugraheni Mardi (Universitas Muhammadiyah Metro, 2023)
Impulse buying is irrational buying behavior because it is less able to make careful consideration before buying, which is supported by a strong desire from within without thinking about its use. Impulse buying is influenced by several factors, one of which is selfregulation. The purpose of this study was to determine the relationship between selfregulation and the impulsive buying of young K-pop fans in purchasing K-pop merchandise. The participants in this study were 204 young K-pop fans aged 18-21 years. The sampling technique used is incidental sampling technique. The scales used in this study are the SelfRegulation Questionnaire (SRQ) and Impulsive Buying Tendency (IBT scale), and the questionnaires are distributed online. The results of research using the Pearson Product Moment Technique showed that there was a weak correlation with a negative relationship between self-regulation and impulsive buying, with a value of r = -0.352 with a significance value of 0.000 (p <0.05), which means that the more individuals have higher self-regulation higher, the lower the impulse buying, or vice versa. So it can be concluded that to have low impulsive buying behavior, young K-pop fans need to have high self-regulation.